SWOT Analysis in a Maritime Higher Education Institution: Strategic Planning Basis for Institutional Efficiency - Victoria Q. Paraggua; Froilan D. Mobo; Ronalyn C. Acuavera; Leah R. Villavicencio; Geraldine C. Pasa; Sheena Lee R. Atejera (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Higher education institutions conduct strategic planning to attain their goals and enhance their operations. Aiming for improved institutional efficiency, the Philippine Merchant Marine Academy (PMMA) conducted SWOT analysis to help establish an effective strategic plan. This quantitative-descriptive study, contributes to the understanding of the Strengths, Weaknesses, Opportunities and Threats (SWOT) affecting the operations of PMMA as a maritime higher education institution. Using a Likert Scale survey questionnaire, the data gathered from 767 respondents revealed that deliberate changes must be made to facilitate institutional growth. The PMMA’s strengths showed that the academy is meeting its objectives and its weaknesses are primarily process driven issues that need attention. The academy’s opportunities are external essentials that provide better chances and options for midshipmen to progress through their academic and training experiences. Most of the respondents agreed that the Academy has threats related to the ongoing COVID-19 pandemic and other future health crisis. To face many challenges brought by the globalization and the pandemic, PMMA has to develop a strategic approach based on the SWOT Analysis leading to improved efficiency. This initiative is meant to institutionalize SWOT analysis at the PMMA and encourage the practice of SWOT analysis in other higher education sectors.